Evaluating the Impacts of Discharging the Effluent of Al-Gabal Al-Asfar Wastewater Treatment Plant on Ismailia Canal in Egypt to Maximize Revenue and Ensure Sustainability - Marwa M Aly; Mohamed SM Zayed; Mahmoud S Salem; Mohamed K Mostafa (Air, Soil and Water Research)
This study seeks to examine the impact of directly releasing the treated wastewater from Al-Gabal Al-Asfar WWTP into Ismailia Canal, Egypt, and evaluate how the discharged water affects the water quality and quantity of Ismailia Canal. The HECRAS 1D model is employed to model water quantity, whereas the QUAL2K model is applied to assess the water quality parameters including dissolved oxygen (DO), pH, biological oxygen demand (BOD), chemical oxygen demand (COD), total phosphorus (TP), nitrate nitrogen (NO 3 -N), and ammonium (NH 4 -N). In the winter and summer of 2023, five scenarios were evaluated with a discharge flow varying from 1.15 to 2.50 Mm 3 /day for the treated water released from Al-Gabal Al-Asfar WWTP, intended for injection into the Ismailia Canal. The optimal scenario was chosen according to the canal water quality post-injection following Article 49 of Law 92/2013, along with the hydraulic capacity of the canal's cross-section. The findings indicated that the fifth scenario (recycling 46% of the treated water, which amounts to 1.15 million cubic meters daily) is the optimal scenario for keeping the concentration of the studied parameters in the Ismailia Canal within the allowable limits and ensuring the canal’s cross-section remains hydraulically secure. Nonetheless, the fourth scenario (reusing 1.50 million cubic meters per day) might be feasible if the efficiency of the plant is enhanced by lowering the ammonium-nitrogen concentration in the effluent. Overall, the suggested solutions can only be implemented if rigorous preventive actions and contingency plans are put into effect on-site. Furthermore, wastewater at Al-Gabal Al-Asfar WWTP must undergo tertiary treatment before its discharge into the Ismailia Canal. The findings of this research may contribute to a decision support system concerning the reuse of treated wastewater in any nation facing water shortages.